Transforming the patient experience: Bringing to life a patient- and family-centred interprofessional collaborative practice model of care at Kingston General Hospital - Anndale McTavish; Cynthia Phillips (The Beryl Institute, 2014)
The Kingston General Hospital strategic plan includes transforming the patient experience and bringing to life new models of interprofessional care and education. The implementation of the Interprofessional Collaborative Practice Model has been the foundation of this transformational change. Areas identified for improvement included communication, discharge planning, and purposeful engagement of patients and families in the care process. Through a system-wide approach to change, it was expected that the organization would be better prepared to deliver safer, higher quality care and enriched experiences for patients, families and practitioners. From March to October 2009, 54 representatives from various disciplines and services gathered to design a new approach to care delivery. The resulting model was conceptualized as a system of interacting levers: People, Technology, Information, and Process. Between November 2009 and April 2012, the model was implemented on 18 inpatient units and 33 ambulatory care areas. Interprofessional collaboration and patient engagement has been vital in optimizing care through this new care delivery model. We quickly came to realize that in order to create and sustain a patient and family-centred approach to care, we needed patients and families to advise us along the way. A Patient and Family Advisory Council was formed in February 2010 and continues to provide direction. Post-implementation results on four units are encouraging, showing improvements in quality of patient care and quality of work life. Continuous monitoring of the changes and using evaluation results to advance the positive changes are the next steps in this transformation of the healthcare experience.